2016
DOI: 10.3390/polym8060209
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of Wheat Straw Alkali Lignin for Application in Phenol Formaldehyde Adhesives

Abstract: Abstract:Lignin is a natural biopolymer with a complex three-dimensional network. It is the second most abundant natural polymer on earth. Commercially, lignin is largely obtained from the waste liquors of pulping and bioethanol productions. In this study, wheat straw alkali lignin (WSAL) was demethylated by using an in-situ generated Lewis acid under an optimized demethylation process. The demethylation process was monitored by a semi-quantitative Fourier Transform Infrared Spectroscopy (FTIR) method. The dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…The presence of severe steric hindrance can extremely diminish the reactivity of lignin. As compared to commercial resins, lignin-modified thermosetting resins such as lignin-phenol-formaldehyde resins and lignin-urea-formaldehyde resins require a higher temperature or more time to achieve the curing [25,26]. Therefore, it is attractive but still challenging to use lignin as fillers in UF resins to effectively improve the reactivity of lignins.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of severe steric hindrance can extremely diminish the reactivity of lignin. As compared to commercial resins, lignin-modified thermosetting resins such as lignin-phenol-formaldehyde resins and lignin-urea-formaldehyde resins require a higher temperature or more time to achieve the curing [25,26]. Therefore, it is attractive but still challenging to use lignin as fillers in UF resins to effectively improve the reactivity of lignins.…”
Section: Introductionmentioning
confidence: 99%
“…PU foams synthesized from the modified Kraft lignins showed a higher compressive strength than conventional ones [36,37]. Song et al used the same method for white straw alkali lignin, with results that showed a significant increase in the total hydroxy content of demethylated lignin [38] when samples were explored for the synthesis of bio-based PF resins by demethylations with sulfur-containing compounds (sulfur, n-dodecyl mercaptan, sodium hydrogen sulfide and sodium sulfite). Here, soda lignin was heated with the reagent for 1 h at 90 • C. This research aimed to provide a cost-effective and efficient method for the chemical demethylation of lignin.…”
mentioning
confidence: 99%
“…Lignin, the second richest renewable material next to cellulose, has been utilized for many applications including bio‐based plastics, polyurethane foams, green antioxidant, flame‐retardant additive, and carbon fibers . Many researchers have been reported lignin‐based resins by blending with phenol, polyethylene oxide, and polyvinyl alcohol (PVA) . They enhances adhesion performance, strongly related to high specific surface area and reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Many researchers have been reported lignin-based resins by blending with phenol, polyethylene oxide, and polyvinyl alcohol (PVA). [13][14][15][16][17][18][19][20] They enhances adhesion performance, strongly related to high specific surface area and reactivity. Epoxy and phenol are most commonly investigated ways to utilize lignin as resin.…”
Section: Introductionmentioning
confidence: 99%